Strain elastography in placental dysfunction: placental elasticity differences in normal and preeclamptic pregnancies in the second trimester - YOLDEMİR, AHMET TEVFİK (SPRINGER HEIDELBERG, 2015)
The aim of this study is to determine if the Strain elastography (SE) of the placenta measured in the second trimester differs between normal pregnancies and pregnancies complicated by preeclampsia (PE). 219 singleton pregnancies who had routine anomaly scanning between the 20th and 23rd weeks of gestation were included in this observational study. Women with either posterior placentations (n = 63) or other obstetric pathologies (n = 12) were excluded from the study, leaving 144 pregnant women for the evaluation of strain ratio with SE. One hundred and one women with normal pregnancies and normal deliveries without any perinatal complications formed Group A. Twenty-eight patients who were clinically diagnosed with early onset PE before anomaly scanning formed Group B. Fifteen normotensive pregnant women with either mild proteinuria, and past history of preeclampsia during their previous pregnancies formed Group C. The strain ratios were compared between the groups. The strain ratio of Group B was significantly higher than those of Group A and Group C (p < 0.05). The placental elasticity ratios measured by SE imaging during the second trimester differ between the normal pregnancies and the pregnancies complicated by PE. SE might be used as a supplement tool in addition to the existing methods for the prediction of PE.
Keywords: Sonoelastography; Placental elasticity; Placental dysfunction; Preeclampsia; Strain; Real-time elastography; REAL-TIME ELASTOGRAPHY; UTERINE ARTERY DOPPLER; FOR-GESTATIONAL-AGE; GROWTH RESTRICTION; ULTRASOUND; MULTICENTER; HYPERTENSION; PREDICTION; DIAGNOSIS; DELIVERY